By the route of sillar. Añashuayco and Culebrillas, Arequipa’s quarries - Málaga Núñez-Zeballos, Alejandro (2017)
The city of Arequipa, was honored by UNESCO as Cultural World Heritage in November 2000, in consideration of the buildings that make up the Cercado in its old neighborhoods, defined as Monumental Zone   and   categorized   as:   Religious   monuments,   military   monuments,   public   monuments   and   domestic monuments. All of them share an element that was already used in buildings constructed by andinas societies before the arrival of the conquerors, the sillar. In this article we will see the main input of the buildings that for over 500 years is continuing to be used, acting as a key element of regional identity, and the proposal to put a value to the quarries of sillar, with a touristic thematic route that has been implemented.